2008
DOI: 10.1292/jvms.70.419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Amounts of Endotoxin Released from Escherichia coli after Exposure to Antibiotics and Ozone: an In Vitro Evaluation

Abstract: ABSTRACT. Antibiotic therapy administered for treatment of gram-negative bacterial infections can exert a negative effect in the form of endotoxin shock. Therefore, a sterilization method that releases little endotoxin is required. This in vitro study aimed to compare the amounts of endotoxin released from Escherichia coli exposed to antibiotics (aminobenzylpenicillin, kanamycin, oxytetracycline, sulfadimethoxine and enrofloxacin) or ozone. The bacterial growth and amount of endotoxin released were measured at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
1
18
1
Order By: Relevance
“…These results, for the first time, indicated that the physical elimination of both microorganisms and endotoxins from the mammary glands by flushing might be essentially important, rather than the sterilization effect of irrigation fluids. Although we recently confirmed using in vitro evaluation that ozone exposure decreases the amount of endotoxins released from E. coli [18], we could not confirm the efficacy of ozone water in the in vivo evaluation in the present field study.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…These results, for the first time, indicated that the physical elimination of both microorganisms and endotoxins from the mammary glands by flushing might be essentially important, rather than the sterilization effect of irrigation fluids. Although we recently confirmed using in vitro evaluation that ozone exposure decreases the amount of endotoxins released from E. coli [18], we could not confirm the efficacy of ozone water in the in vivo evaluation in the present field study.…”
Section: Discussioncontrasting
confidence: 83%
“…However, our previous study demonstrated that the amounts of induced-endotoxin induced by bacteriostatic antibiotics were not different from those by bactericidal antibiotics [18]. Moreover, in farm animal practices, the impact of antibiotic use has recently been considered to be important not only for preventing the emergence of drug resistance but also from the viewpoint of food safety and public health [16].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…These gram negative microbes tend to develop endotoxic shock upon treatment with antibiotics. A study was conducted to compare the amount of endotoxin produced upon antibiotic therapy and ozone therapy.Results showed that in comparison to antibiotic therapy, ozone therapy (0.8mg/L) resulted in less amount of endotoxin production (Shinozuka et al, 2008). It is observed that ozone therapy helps in reversing the local and systemic signs of acute clinical mastitis in animals.…”
Section: Clinical Mastitis In Maresmentioning
confidence: 98%
“…Lipopolysaccharide (LPS), an endotoxin in Gram‐negative bacteria, can activate the Toll‐like receptor 4 (TLR4) signaling pathway and promote the production of inflammatory mediators, such as tumor necrosis factor (TNF)‐α, that would likely lead to endothelial damage and systemic inflammatory response syndrome . As most antibiotics facilitate the release of LPS while killing bacteria, using AMPs that are able to suppress the pro‐inflammatory effect of LPS to eliminate bacteria is a well‐balanced strategy. HD5 is a lectin‐like molecule that can multivalently bind to carbohydrates .…”
Section: Introductionmentioning
confidence: 99%